I feel Kind why do I feel kind today? - Braddon, Amy; Day, Teresa; Flynn, Sonny (London Dorling Kindersley Limited, 2021)
Help little ones learn about their emotions and discover kindness in this sweet little board book. I Feel Kind is the perfect introduction to kindness, teaching youngsters how little acts of kindness in everyday life can have a positive impact on themselves and others. Follow the story of the bright Kind flower to see how kindness looks and feels and the many ways children can spread kindness
Linguistic notions
Keywords: Board books; Emotions; picture books